SINTESIS DAN KARAKTERISASI SENYAWA KOMPLEKS Zn(II)-EDTA SEBAGAI SENAYAWA ANTIALGA PADA COOLING WATER INDUSTRI - Harsasi Setyawati; Sri Sumarsih; Sevia Ayuningtyas (Jurnal Kimia Riset, 2017)
ABSTRACTA research on the synthesis and characterization of complex compounds of Zn (II)-EDTA as antialgae compound is applied to the cooling water industry. This research aims to determine the activity of complex compounds of Zn (II)-EDTA against algae that live in the water cooling water. The activity antialgae assay of comple compound of Zn(II)-EDTA with luminescence method and dry cell weight method. Complex compound of Zn (II)-EDTA made with mole ratio of ZnCl2: Na2EDTA is 1:1. Complex compound of Zn (II)-EDTA analyzed using UV-Vis spectrophotometer and FTIR spectrophotometer. The results of UV-Vis spectrophotometer analysis showed that the complex compounds of Zn (II)-EDTA has a maximum wavelength at 752 nm. While the results of FTIR analysis showed  Zn-O vibration absorption at wave number 478.35 cm-1 and Zn-N vibration absorption at wave number 516.92 cm-1. In the activity antialgae assay of complex compound of Zn (II)-EDTA made with a concentration of 5 ppm, 10 ppm, 50 ppm and 100 ppm. The test results showed that the activity of complex compounds of Zn (II) -EDTA can kill green algae and brown algae. Of the four concentrations of complex compounds of Zn (II)-EDTA, green algae and brown algae can be killed optimally at a concentration of 50 ppm.Keywords: complex Zn(II)-EDTA, cooling water, antialgae, green algae, brown                   algae